Tom Nauerby: No Nation Is an Island. Language, Culture, and National Identity in the Faroe Islands - Pedersen, Bent (Tidsskriftet Antropologi, 1999)
Language, Culture, and National Identity in the Faroe Islands. Anmeldes af Bent Pedersen